The effect of antimicrobial agents on bond strength of orthodontic adhesives: a meta‐analysis of in vitro studies. (10th August 2015) - Altmann, A. S. P.; Collares, F. M.; Leitune, V. C. B.; Samuel, S. M. W.
Abstract: Antimicrobial orthodontic adhesives aim to reduce white spot lesions' incidence in orthodontic patients, but they should not jeopardizing its properties. Systematic review and meta‐analysis were performed to answer the question whether the association of antimicrobial agents with orthodontic adhesives compromises its mechanical properties and whether there is a superior antimicrobial agent. PubMed and Scopus databases. In vitro studies comparing shear bond strength of conventional photo‐activated orthodontic adhesives to antimicrobial photo‐activated orthodontic adhesives were considered eligible. Search terms included the following: orthodontics, orthodontic, antimicrobial, antibacterial, bactericidal, adhesive, resin, resin composite, bonding agent, bonding system, and bond strength. The searches yielded 494 citations, which turned into 467 after duplicates were discarded. Titles and abstracts were read and 13 publications were selected for full‐text reading. Twelve studies were included in the meta‐analysis. The global analysis showed no statistically significant difference between control and experimental groups. In the subgroup analysis, only the chlorhexidine subgroup showed a statistically significant difference, where the control groups had higher bond strength than the experimental groups. Many studies on in vitro orthodontic bond strength fail to report test conditions that could affect their outcomes. The pooled in vitro data suggest that adding an antimicrobial agent to an orthodontic adhesive system does not influence bond strength to enamel. It is not possible to state which antimicrobial agent is better to be associated.